2013
DOI: 10.1089/ars.2013.5330
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Kinase Signal Modulation: A Matter of H2O2 Membrane Permeability?

Abstract: H 2 O 2 produced by extracellular NADPH oxidases regulates tyrosine kinase signaling inhibiting phosphatases. How does it cross the membrane to reach its cytosolic targets? Silencing aquaporin-8 (AQP8), but not AQP3 or AQP4, inhibited H 2 O 2 entry into HeLa cells. Re-expression of AQP8 with silencing-resistant vectors rescued H 2 O 2 transport, whereas a C173A-AQP8 mutant failed to do so. Lowering AQP8 levels affected H 2 O 2 entry into the endoplasmic reticulum, but not into mitochondria. AQP8 silencing also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(93 citation statements)
references
References 9 publications
2
90
1
Order By: Relevance
“…These data confirmed that H 2 O 2 acts as a rheostat of tyrosine kinase signaling and demonstrated that AQP8 guarantees efficient cytosolic import of H 2 O 2 likely produced by NOXes. AQP8 silencing inhibited, in part, the transport of H 2 O 2 through the ER membrane, but had little if any effect on mitochondria (6), where a fraction of AQP8 has been reported to localize (9). In other cell types, AQP3 (18,39) and possibly different channels can allow efficient H 2 O 2 transport.…”
Section: Innovationmentioning
confidence: 98%
See 1 more Smart Citation
“…These data confirmed that H 2 O 2 acts as a rheostat of tyrosine kinase signaling and demonstrated that AQP8 guarantees efficient cytosolic import of H 2 O 2 likely produced by NOXes. AQP8 silencing inhibited, in part, the transport of H 2 O 2 through the ER membrane, but had little if any effect on mitochondria (6), where a fraction of AQP8 has been reported to localize (9). In other cell types, AQP3 (18,39) and possibly different channels can allow efficient H 2 O 2 transport.…”
Section: Innovationmentioning
confidence: 98%
“…Recently, members of the aquaporin protein family (AQP), initially described as bidirectional water transporters (1), have been found to channel also H 2 O 2 (7). We have recently shown that aquaporin-8 (AQP8) is essential to allow effective transport of H 2 O 2 across the plasma membrane, thus potentiating tyrosine phosphorylation induced by growth factors (6), a notion later corroborated by others (57). These data confirmed that H 2 O 2 acts as a rheostat of tyrosine kinase signaling and demonstrated that AQP8 guarantees efficient cytosolic import of H 2 O 2 likely produced by NOXes.…”
Section: Innovationmentioning
confidence: 99%
“…This topological problem is solved by membrane-embedded aquaporin channels (AQPs). By serving as H 2 O 2 pores they facilitate the formation of local areas with an elevated H 2 O 2 concentration on both sides of the plasma membrane [13][14][15][16].…”
Section: Principles Of Reduction-oxidation Signalingmentioning
confidence: 99%
“…AQP8 fulfills a major function in the transport of H 2 O 2 at the plasma membrane [13]. In addition, knockdown of AQP8 strongly diminishes the entry of exogenous H 2 O 2 into the ER of plasma membrane-permeabilized cells [13].…”
Section: Aquaporins Regulate the Permeability Of The Er Membrane To Hmentioning
confidence: 99%
“…Hydrogen peroxide molecule is similar to water, thus it is not surprising that the water channel aquaporins can also facilitate the traffic of hydrogen peroxide across cellular membranes [129]. Specific aquaporins -peroxiporinsare especially engaged in hydrogen peroxide transport [129,130], and some representatives of these hydrogen peroxide-channels are present in the ER membrane. However, the actual direction of hydrogen peroxide flux has not been elucidated.…”
Section: Formation and Elimination Of Hydrogen Peroxide In The Ermentioning
confidence: 99%